Diagnostic Justice: Testing for Covid-19 - Ashley Graham Kennedy (University of Rijeka. Faculty of Humanities and Social Sciences, 2021)
Diagnostic testing can be used for many purposes, including testing to facilitate the clinical care of individual patients, testing as an inclusion criterion for clinical trial participation, and both passive and active surveillance testing of the general population in order to facilitate public health outcomes, such as the containment or mitigation of an infectious disease. As such, diagnostic testing presents us with ethical questions that are, in part, already addressed in the literature on clinical care as well as clinical research (such as the rights of patients to refuse testing or treatment in the clinical setting or the rights of participants in randomized controlled trials to withdraw from the trial at any time). However, diagnostic testing, for the purpose of disease surveillance also raises ethical issues that we do not encounter in these settings, and thus have not been much discussed. In this paper we will be concerned with the similarities and differences between the ethical considerations in these three domains: clinical care, clinical research, and public health, as they relate to diagnostic testing specifically. Via an examination of the COVID-19 case we will show how an appeal to the concept of diagnostic justice helps us to make sense of the (at times competing) ethical considerations in these three domains.